Prevalence of male pelvic dysfunction: results from the Turkish society of andrology male sexual health study group - Kendirci, M.; Asci, R.; Yaman, O.; Cayan, S.; Orhan, I.; Usta, M. F.; Kadioglu, A. (Wiley-Blackwell, 2014)
The objective of this study was to determine the prevalence of male pelvic dysfunction (MPD) and its correlation in men 40years of age in a population-based study. This study was designed as a non-interventional, observational, cross-sectional field survey. Participating males of 40years were randomly selected from 19 provinces of Turkey. All participants were asked to complete a survey including data regarding demographics, socio-economic status, socio-cultural factors, medical and sexual history, current medications, comorbidities and three validated questionnaires assessing lower urinary tract symptoms (International Prostate Symptom Score), erectile dysfunction (International Index of Erectile Function) and ejaculatory behaviour (Male Sexual Health Questionnaire-4). MPD was defined by combining abnormal scores calculated from all three questionnaires. All data were analysed statistically and p<0.05 was accepted as significant. A total of 2730 males of 40years (mean, 54.2 +/- 10.6years) were enrolled in this study. The prevalence of MPD was calculated as 24.4% among all participants. The prevalence of MPD was lowest at age between 40 and 49years (9.1%) and highest at 70years (76.6%), exhibiting correlation with age. Each decade of increase in age was associated with a 3.4-fold increase in presence of MPD. At logistic regression analyses; age, diabetes, hypertension, dyslipidemia, cardiovascular disease, obesity and lower income were found to be independent predictors for increased prevalence of MPD. This study reports prevalence of MPD as 24.4% in males of 40years. Furthermore, age was found to be the main independent predictor of having MPD.
Keywords: benign prostatic hyperplasia; ejaculatory dysfunction; erectile dysfunction; lower urinary tract symptoms; male pelvic dysfunction; men's health